PENGARUH UKURAN PERUSAHAAN, DEBT TO EQUITY RATIO DAN KEPEMILIKAN PUBLIK YANG MEMPENGARUHI KETEPATAN WAKTU PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA 2011-2016 - Elsya Meida Arif; Steffi Anita (Jurnal Manajemen FE-UB, 2018)
This research was conducted on Banking Company. The purpose of this study was to examine the effect of firm size, debt to equity ratio and public ownership on the timeliness of corporate financial reporting. This study used a sample of banking companies listed on the Indonesia Stock Exchange during 2011 to 2016. The sampling method used was purposive sampling method. The number of companies sampled in this study were 10 companies with observations for six years, so the sample selected was 60 companies. The data used is secondary data. The statistic method used is multiple linear regression analysis using Eviews 8. Hypothesis test is done by using F test and t test with significance α = 0,05. The results of this study show that jointly (at the same time) firm size, debt to equity ratio and public ownership contribute and have a significant influence on the timeliness of financial reporting at Banking Company of 95.97% with adjusted R2 of 0.8959729 . Partially, firm size, debt to equity ratio and public ownership contribute and have a significant influence on the timing of the Banking Company. Keywords: Company Size, Debt to Equity Ratio, Public Ownership, Timeliness